Cushioning and lateral stability functions of cloth sport shoes - Fong, D. T. P.; Hong, Y.; Li, J. X. (Sports Biomechanics, 2007)
In this study, we evaluated the protective functions of cloth sport shoes, including cushioning and lateral stability. Twelve male students participated in the study (mean ± s: age 12.7 ± 0.4 years, mass 40.7 ± 5.9 kg, height 1.50 ± 0.04 m). Cloth sport shoes, running shoes, basketball shoes, cross-training shoes, and barefoot conditions were investigated in random sequence. Human pendulum and cutting movement tests were used to assess cushioning performance and lateral stability, respectively. For cushioning, the running shoes (2.06 body weight, BW) performed the best, while the cross-training shoes (2.30 BW) and the basketball shoes (2.37 BW) both performed better than the cloth sport shoes (2.55 BW) and going barefoot (2.63 BW). For the lateral stability test, range of inversion-eversion was found to be from 3.6 to 4.9°, which was far less than that for adult participants (> 20°). No significant differences were found between conditions. All conditions showed prolonged durations from foot-strike to maximum inversion (66-95 ms), which was less vigorous than that for adult participants ( < 40 ms) and was unlikely to evoke intrinsic stability failure. In conclusion, the cloth sport shoe showed inferior cushioning capability but the same lateral stability as the other sports shoes for children.